2013
DOI: 10.1021/ac303749b
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Chemical Mapping with a Confocal XRF Setup

Abstract: A new approach for the nondestructive reconstruction of stratified systems with constant elemental composition but with varying chemical compounds has been developed. The procedure is based on depth scans with a confocal X-ray fluorescence setup at certain energies near absorption edges. These so-called marker energies, where XAFS signals of the involved chemical compounds differ significantly, can also be used to uncover the chemical composition and its topology. A prominent field of application is homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…To be able to make some assumptions on those unknown elements, the Compton scattering is measured simultaneously. The model is developed by the Work group of B. Kanngießer at the TU Berlin, and works for nite and for layered samples (Kanngießer et al, 2012;Lühl et al, 2013;Mantouvalou et al, 2011). All the capillaries were produced by Institut für Gerätebau Berlin.…”
Section: D Xrf-mappingmentioning
confidence: 99%
“…To be able to make some assumptions on those unknown elements, the Compton scattering is measured simultaneously. The model is developed by the Work group of B. Kanngießer at the TU Berlin, and works for nite and for layered samples (Kanngießer et al, 2012;Lühl et al, 2013;Mantouvalou et al, 2011). All the capillaries were produced by Institut für Gerätebau Berlin.…”
Section: D Xrf-mappingmentioning
confidence: 99%
“…Of course, it also enables a depth elemental profiling. There are many reports of depth elemental profiling for layered materials such as paint layers [29][30][31][32][33][34][35][36][37][38][39]. The author's research group at OCU has reported a depth elemental profile for car paint chips, which have several layers depending on the type of car and manufacturing process [40].…”
Section: Confocal Micro-xrf In the Laboratorymentioning
confidence: 99%
“…In XAFS, the measurement of the X-ray absorption coefficient of a material as a function of energy can be performed with such methods as a fluorescence mode and a transmission detection. Confocal XAFS is based on the fluorescence mode (Lühl et al 2013).…”
Section: Basics Of Confocal Xafsmentioning
confidence: 99%
“…A reliable reconstruction algorithm for obtaining undistorted spectra for superficial and in-depth layers was developed to calculate the attenuation coefficients of the analyte for successive layers, which facilitates a new spectroscopic tool for 3D resolved nondestructive chemical speciation (Lühl et al 2012(Lühl et al , 2013.…”
Section: Experimental Design Of Confocal Xafsmentioning
confidence: 99%